2021
DOI: 10.1016/j.brs.2021.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Cortical plasticity is correlated with cognitive improvement in Alzheimer’s disease patients after rTMS treatment

Abstract: Objective: Repetitive transcranial magnetic stimulation (rTMS) has been widely used in non-invasive treatments for different neurological disorders. Few biomarkers are available for treatment response prediction. This study aims to analyze the correlation between changes in long-term potentiation (LTP)like cortical plasticity and cognitive function in patients with Alzheimer's disease (AD) that underwent rTMS treatment. Methods: A total of 75 AD patients were randomized into either 20 Hz rTMS treatment at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 53 publications
6
95
0
Order By: Relevance
“…This implies that the cognitive improvements in patients under rTMS treatment were not due to alleviation of depressive symptoms. Notably, the findings of the current study showed that rTMSinduced cognitive improvement was reduced at 12-week follow-up in subjects in the treatment group which is consistent with findings from a previous study [50] which reported that 30 sessions comprising 20Hz rTMS treatment over a six-week period in the DLPFC significantly improved cognitive function of patients, although this improvement could not be maintained during a three-month follow up period. This can be attributed to rTMS dosage, and its combination with other therapeutic approaches.…”
Section: Parietal-hippocampal Targeted Rtms Improves Cognitive Function In Alzheimer's Disease Patientssupporting
confidence: 91%
“…This implies that the cognitive improvements in patients under rTMS treatment were not due to alleviation of depressive symptoms. Notably, the findings of the current study showed that rTMSinduced cognitive improvement was reduced at 12-week follow-up in subjects in the treatment group which is consistent with findings from a previous study [50] which reported that 30 sessions comprising 20Hz rTMS treatment over a six-week period in the DLPFC significantly improved cognitive function of patients, although this improvement could not be maintained during a three-month follow up period. This can be attributed to rTMS dosage, and its combination with other therapeutic approaches.…”
Section: Parietal-hippocampal Targeted Rtms Improves Cognitive Function In Alzheimer's Disease Patientssupporting
confidence: 91%
“…Our results showed that the rTMS-induced cognitive improvement in the active-rTMS group disappeared at 12-week follow-up. It was similar to a recent study [49], which reported that 20Hz rTMS treatment for 30 sessions over six weeks in the DLPFC resulted in a significant improvement in cognition, but this improvement was not maintained in the three-month follow up. rTMS dose and its combination with other therapeutic approaches were important issues in this case.…”
Section: Parietal-hippocampal Targeted Rtms Can Improve Cognitive Function In Alzheimer's Diseasesupporting
confidence: 91%
“…rTMS of left dlPFC has produced moderately consistent effects on RSFC but less consistent cognitive outcomes. Regarding cognitive changes associated with left dlPFC rTMS, eight of twelve studies reviewed here reported significant cognitive improvements associated with high-frequency stimulation [14,33,34,37,38,40,41,[43][44][45]70,71]. Further, one study using low-frequency rTMS reported acute cognitive impairment [42].…”
Section: Review Of Prior Work 21 Organization Of the Reviewmentioning
confidence: 72%
“…Fortunately, recent findings suggest that targeted non-invasive brain stimulation (NBS) may offer meaningful opportunities for treatment [10]. Specifically, transcranial magnetic stimulation (TMS), a form of NBS, has been reported to improve memory in healthy younger adults, healthy older adults, and individuals with AD [11][12][13][14]. TMS may therefore hold promise as a potential symptomatic treatment for memory loss.…”
Section: Introductionmentioning
confidence: 99%